Application of the theory of para-social relationships for the analysis of people’s perceptions of indoor plants - Elizaveta Ivashkina; Elizaveta Ivashkina; Oxana Mikhaylova (Frontiers in Psychology)
IntroductionDespite extensive research on the psychological and environmental benefits of houseplants, little is known about how individuals perceive and form emotional connections with them. This study addresses this gap by applying the theory of para-social relationships (PSRs)—traditionally used to analyze one-sided bonds with media figures—to human-plant interactions.MethodsFifteen semi-structured, in-depth interviews were conducted with Russian-speaking university students who demonstrated close bonds with their indoor plants. The interviews explored the initiation, maintenance, and influencing factors of PSRs with plants, focusing on personal experiences and contextual variables.ResultsKey findings reveal that exposure, homophily (perceived similarity), and contextual factors such as urban living and personal space are critical in fostering these relationships. Participants described engaging in regular care, observation, tactile interaction, and anthropomorphism to deepen their connections with plants. Five distinct types of human-plant relationships were identified: ownership, friendship, parenthood, sibling-like bonds, and neighborly relations, each varying in intensity and perceived plant agency.DiscussionThe study highlights the therapeutic potential of PSRs with indoor plants in mitigating stress, enhancing emotional well-being, and providing companionship—particularly for students navigating transitional life stages or living in isolating environments like dormitories. These findings have broader implications for horticultural therapy, environmental psychology, and urban biophilic design. By extending PSR theory beyond human-media contexts to include non-human entities like plants, this research underscores the importance of fostering meaningful connections with nature to support mental health and promote sustainable living practices.